Molecular evaluation of genetic diversity and relationships of Musa cultivars in Thailand using Start Codon Targeted (SCoT) markers - SARUDA NITIWORAKARN; WUTTICHAI PHAE-NGAM; ONGKARN VANIJAJIVA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Nitiworakarn S, Phae-Ngam W, Vanijajiva O. 2023. Molecular evaluation of genetic diversity and relationships of Musa cultivars in Thailand using Start Codon Targeted (SCoT) markers. Biodiversitas 24: 4060-4068. Musa cultivars are mostly obtained from crossing between wild diploid subspecies of M. acuminata (A genome) and M. balbisiana (B genome), and they reveal numerous levels of ploidy and genomic constitution. The present study, for the first time, investigated the genetic diversity of 90 Musa cultivars from 17 localities of Chai Badan district in Lopburi Province, Thailand, using start codon targeted (SCoT) markers. The SCoT technique has shown very high repeatability for characterizing Musa cultivars. The result indicated that DNA fingerprints from 30 SCoT primers generated 244 amplicons, among which 238 bands (97.54%) were polymorphic, with a mean of 7.93 polymorphic bands per primer. The average polymorphism information content (PIC) was high, ranging from 0.345 to 0.483, with an average of 0.432. Genetic diversity and its partitioning parameters were calculated and demonstrated that present Musa cultivars maintain relatively high genetic diversity. The unweighted pair-group method with an arithmetic cluster analysis, principal coordinate analysis and STRUCTURE analysis results were the same and showed the clear division of the genotypes into two distinct clusters, which were cluster-I consisted of only the AA genomes and cluster-II comprised of ABB and BB genomes. In conclusion, SCoT markers obtained here showed their manipulation in genetic diversity and the relationship of cultivated Musa, which would be practical for genetic preservation and continuing breeding programs in Thailand and other regions.